2014
DOI: 10.1167/iovs.14-13889
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Chaperonin CCT in Rod Outer Segment Biogenesis

Abstract: Our data provide new evidence indicating the essential role of the chaperonin CCT in the biogenesis of vertebrate photoreceptor sensory cilia, and suggest that it may be due to the direct participation of the chaperonin in the posttranslational processing of selected BBS proteins and assembly of the BBSome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…To date, the only data reported on the amphibian homologue of TCP1 concern the expression of tcp1a (CCTa) in the axolotl (Ambystoma mexicanum), in which it is spatially and temporally regulated during neural and somitic development (Sun et al, 1995), and the expression in Xenopus laevis embryos of tcp1a and tcp1g, which appear to be developmentally regulated in neural-derived and myogenic lineages (Dunn and Mercola, 1996). Recently, we selected pfdn6a and tcp1a in the course of a screen aimed at identifying genes coherently controlled by the retinal key regulator Rx1 (Giannaccini et al, 2013;Giudetti et al, 2014), consistently with previous data indicating a role of PFDN and TCP1 in retinal development (Matsuda and Mishina 2004;Lee et al, 2011Sinha et al, 2014. The coregulation of these two genes by Rx1 suggested that they could display a general coordinated expression during embryogenesis.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…To date, the only data reported on the amphibian homologue of TCP1 concern the expression of tcp1a (CCTa) in the axolotl (Ambystoma mexicanum), in which it is spatially and temporally regulated during neural and somitic development (Sun et al, 1995), and the expression in Xenopus laevis embryos of tcp1a and tcp1g, which appear to be developmentally regulated in neural-derived and myogenic lineages (Dunn and Mercola, 1996). Recently, we selected pfdn6a and tcp1a in the course of a screen aimed at identifying genes coherently controlled by the retinal key regulator Rx1 (Giannaccini et al, 2013;Giudetti et al, 2014), consistently with previous data indicating a role of PFDN and TCP1 in retinal development (Matsuda and Mishina 2004;Lee et al, 2011Sinha et al, 2014. The coregulation of these two genes by Rx1 suggested that they could display a general coordinated expression during embryogenesis.…”
supporting
confidence: 82%
“…In mouse, tcp1a is observed at the morula and blastocyst stages and its expression is higher in post implantation embryos than in any adult organs except testis, indicating that tcp1a expression is regulated spatially and temporally during embryogenesis (Kubota et al, 1992). Finally, suppression of TCP1 activity in mouse photoreceptors leads to malformation of the outer segments and triggers retinal degeneration, indicating an essential role of TCP1 in the differentiation and survival of this photosensitive cell type (Sinha et al, 2014).…”
mentioning
confidence: 99%
“…Chaperone T-complex protein 1 has been extensively studied in humans and animals (Sinha et al, 2014; Wu et al, 2015), but the function of chaperone T-complex protein 1 remains poorly understood in plants. In this study, drought significantly elevated the expression of T-complex protein 1 subunits zeta (B6U118) and delta (C0HGT5) in an ABA-dependent way.…”
Section: Discussionmentioning
confidence: 99%
“…One group of the HSP70 family, CCT (Chaperonin containing Tcp1), was shown to be essential for elongation and extension of the rod outer segments, i.e. mice deficient in CCT were unable to build outer segments due to the impairment of ciliary trafficking (Posokhova et al, 2011; Sinha et al, 2014). It has been reported that tubb y mice exhibited blockage of transport of selective G protein-coupled receptors (GPCRs) to the neuronal primary cilia and aberrant rhodopsin trafficking, indicating that the Tubby protein is a required part of the transport machinery in retinal cells (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%